A parceria entre Estado e as organizações sociais por meio de convênio para execução da assistência social no Grajaú – São Paulo - SP - Souza, Elaine dos Santos (2017)
This research, motivated by the insufficiency of studies that portray the reality of SASF's social assistance service in the Grajaú district, seeks to understand and problematize the execution of this service through a partnership between the State and social organizations, in compliance with the objectives of the Single System of Social Welfare (SUAS). It is hypothesized that the agreement process designed for the public policy of Social Assistance presupposes processes of flexibilization under the logic of outsourcing, contributing to spaces of precarious work and possible brands of conservatism present in social organizations. The methodological path traced, guided by the critical social theory, sought to understand the historical movement and its complexity, using the qualitative research with semi-structured interview and bibliographical research. The data were systematized and grouped into axes, allowing to perform analysis that demonstrated congruent and divergent points. With this analytical course, the dissertation was organized in four chapters. Chapter I briefly contextualized the social protection models of European countries and the United States, in order to outline the characteristics that are present in the Brazilian social policy analyzed in this research. Chapter II sought to historicize the legal frameworks of Social Assistance, after its recognition as social policy of law, elucidating the management and implementation of SUAS in the City of São Paulo, in different municipal governments. Chapter III discusses the growth of the socio-welfare network in the city from the partnerships with social organizations, presenting the working conditions of the contracted professionals and the logic of the outsourcing of the policy, implicated in the SASF executing the PAIF. Chapter IV presents the services deployed in Grajaú, with a cut in SASF Grajaú IV presenting the field interviews systematized through the analytical axes. The Final Considerations conclude this Dissertation